Activation cross section for the (n,2n) reaction on 197Au - Kalamara, A.; Serris, M.; Anastasiou, M.; Diakaki, M.; Kokkoris, M.; Patronis, N.; Paneta, V.; Axiotis, M.; Lagoyannis, A.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2019)
The cross section of the reaction channels 197Au(n,2n)196Aug+m1 and 197Au(n,2n)196Aum2 has been experimentally determined at 15.3 MeV, relative to the 27Al(n,α)24Na reference reaction, using the activation technique. The irradiation was carried out at the 5 MV tandem T11/25 Accelerator Laboratory of NCSR "Demokritos" with monoenergetic neutron beam provided by means of the 3H(d,n)4He reaction, using a new Ti-tritiated target of 373 GBq activity. The induced γ- ray activity was measured with a high resolution HPGe detector.